ELECTION OF LEADERS IN MUSLIM MINORITY AREAS: THE PERSPECTIVE OF MAQĀṢID AL-SYARĪ‘AH ON THE AUTHORITY OF THE PAPUAN PEOPLE'S ASSEMBLY - Sabar Podu; Lukman Ansar; Tarmizi Tarmizi; Zulfadli Zulfadli; Dewi Arnita Sari (Institut Agama Islam Negeri Bone, 2026)
The Papuan People’s Assembly (MRP) has the constitutional authority to provide input in the selection of regional leaders as a means of protecting the rights of the indigenous Papuan people (OAP). However, the implementation of this authority poses a unique challenge in regions with Muslim minorities, which are characterized by religious and ethnic pluralism as well as local political dynamics. This study aims to analyze the role of the MRP in the election of regional leaders through the perspective of maqāṣid al-syarī‘ah as an inclusive ethical framework for public policy. This study employs a qualitative approach with a literature review design and descriptive analysis of legal texts, legal literature, political literature, and contemporary concepts of maqāṣid. The research findings indicate that the principles of maqāṣid, particularly the protection of life, mind, and the public welfare, are relevant for evaluating the ethical considerations of the MRP without turning it into an instrument of religious exclusivism. The contribution of this study lies in the development of maqāṣid al-syarī‘ah as an interfaith ethical framework in regional leadership governance and the strengthening of the MRP’s normative legitimacy within the context of Papuan pluralism. This study concludes that the maqāṣid approach is capable of bridging Papuan customary values and democratic principles to promote justice, inclusivity, and social harmony.